2007
DOI: 10.1111/j.1478-3231.2007.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Doppler ultrasound in the prediction of severe portal hypertension in hepatitis C virus‐related chronic liver disease

Abstract: Superior mesenteric artery pulsatility index, intraparenchymal splenic and right interlobar renal artery resistance indices do not adequately predict severe portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 33 publications
0
21
1
2
Order By: Relevance
“…Moreover, studies carried out by Vizzutti et al, [21] a cutoff value for prediction of varices was 17.6 kPa, these cut off values are smaller than we obtained, but the different demographics and patients characteristics as well as the type of fibroscan machines could be the reason for these discrepancy. More over Castera L et al, [22] showed that Transient elastography could be a valuable tool in diagnosis of cirrhosis but cannot replace endoscopy for variceal screening.…”
Section: Discussioncontrasting
confidence: 90%
“…Moreover, studies carried out by Vizzutti et al, [21] a cutoff value for prediction of varices was 17.6 kPa, these cut off values are smaller than we obtained, but the different demographics and patients characteristics as well as the type of fibroscan machines could be the reason for these discrepancy. More over Castera L et al, [22] showed that Transient elastography could be a valuable tool in diagnosis of cirrhosis but cannot replace endoscopy for variceal screening.…”
Section: Discussioncontrasting
confidence: 90%
“…Apart from the technique of performing DDUS, factors which could explain the discrepancy amongst different studies include etiology of cirrhosis, Child Turcotte Pugh (CTP) stage of disease, presence or absence of variceal bleeding, exclusion criteria particularly current medications and co-morbidities (Table 4). Arterial indices are less prone to variability and are more reproducible compared to venous indices [44]. This factor could also be responsible as all studies did not measure the arterial indices.…”
Section: Comparison Of Ddus and Hvpg In Assessment Of Ppmentioning
confidence: 97%
“…The literature on this at present are conflicting (Table 4) [27,28,39,40,[44][45][46][47][48][49]. Apart from the technique of performing DDUS, factors which could explain the discrepancy amongst different studies include etiology of cirrhosis, Child Turcotte Pugh (CTP) stage of disease, presence or absence of variceal bleeding, exclusion criteria particularly current medications and co-morbidities (Table 4).…”
Section: Comparison Of Ddus and Hvpg In Assessment Of Ppmentioning
confidence: 97%
“…Doppler ultrasound is clinically used to perform velocity measurements in the portal vein or any vessel of interest in the mesenteric circulation, however, it is limited in its ability to accurately measure cross-sectional area and hence true flow through the vessel (43). Additionally, Iwao et al have reported high interobserver variability for portal venous flow with a correlation coefficient of only 0.49 (44).…”
Section: Discussionmentioning
confidence: 99%